2022
DOI: 10.3389/fnhum.2022.943976
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological indices of pain expectation abnormalities in fibromyalgia patients

Abstract: Fibromyalgia is a chronic pain syndrome characterized by dysfunctional processing of nociceptive stimulation. Neuroimaging studies have pointed out that pain-related network functioning seems to be altered in these patients. It is thought that this clinical symptomatology may be maintained or even strengthened because of an enhanced expectancy for painful stimuli or its forthcoming appearance. However, neural electrophysiological correlates associated with such attentional mechanisms have been scarcely explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 131 publications
0
3
0
Order By: Relevance
“…The main finding of this study highlights the complex pathophysiological mechanisms that underlie fibromyalgia, including alterations in neurotransmission [ 4 , 6 , 22 , 98 ], perception modulation [ 2 , 100 , 104 ], environmental stress [ 6 , 54 , 107 ], and epigenetic modifications [ 17 , 110 , 112 , 113 , 114 ], all of which may affect the EBA [ 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main finding of this study highlights the complex pathophysiological mechanisms that underlie fibromyalgia, including alterations in neurotransmission [ 4 , 6 , 22 , 98 ], perception modulation [ 2 , 100 , 104 ], environmental stress [ 6 , 54 , 107 ], and epigenetic modifications [ 17 , 110 , 112 , 113 , 114 ], all of which may affect the EBA [ 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 ].…”
Section: Discussionmentioning
confidence: 99%
“…This sensitivity may be due to alterations in the way that pain signals are processed in the central nervous system. Studies have shown that individuals with fibromyalgia have changes in the way that their brains respond to pain stimuli [ 2 , 3 , 99 , 102 , 103 , 104 , 105 ], which may contribute to the heightened pain sensitivity and chronic pain experienced by these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic pain can have both physical and psychological repercussions for patients, as well as significant healthcare and economic burdens and diminished productivity (11). Patients with chronic pain often face an increased risk of developing complications, including alterations in cognitive processes such as memory and attention (12), changes in brain chemistry and neocortical gray matter (13), and challenges in accurately perceiving chronic pain and related behavioral aspects (14) Chronic pain is linked to elevated rates of major depressive disorder in American adults (15), suicidal ideation and attempts (16), sleep disturbances (17), sexual dysfunction (18), and conditions like hypertension (19). Despite these challenges, maintaining functional abilities despite chronic pain is a key goal of various treatment interventions.…”
Section: Introductionmentioning
confidence: 99%